Health is wealth : health progrmme - Mackenzie, James; Haldane, William S. ([Scotland : Industrial Health Education Council], 1926)
1926 1926 1920s 16 pages 8 Falkirk Town Council Health Committee and Trades and Labour Council — Dr. W. J. Logie and Mr. J.A. Young, L.D.S., Edinburgh. Gifford Women's Rural Institute — Dr. Main, Gifford. Airdrie Miners — Dr. Martyn, Airdrie, and Mr. S. Dunn, L.D.S., Glasgow. Swinhill Miners — Dr. Morrison, Larkhall. Fauldhouse Miners — Dr. Ogilvy, Fauldhouse. Fordell Miners — Dr. Kifkind, Crossgates. Valleyfield Miners — Dr. Wallace, Limekilns. Kirkford Miners — Dr. Primmer, Cowdenbeath. Wishaw Co-operative Women's Guild — Dr. Mary Urquhart, Wishaw. Deerness Women's Rural Institute — Dr. Bannerman, Kirkwall. Hamilton Miners — Dr. Denness, Bothwell, and Dr. Chas. Read, L.D.S., Glasgow. Longniddry Women's Rural Institute — Dr. Christina Mayne, Edinburgh. Kelty Public Library and Miners — Dr. Moir, Kelty. Stoneyburn Miners — Dr. Seward, Stoneyburn. Smeaton Miners — Dr. M'Ewan, Prestonpans. Perth Trades Council — Dr. Hume, Perth. Bellshill Miners — Oakley Miners — Dr. Yuill, Oakley. Stonehouse Miners — Dr. Jarvie. Kennox Miners — Dr. M'Feat, Douglas. Buckhaven Miners — Dr. Ferguson, Buckhaven. Cromdale Women's Rural Institute — Kinlochard Women's Rural Institute — Portree Women's Rural Institute — Dr. Morrison. Portree. Arnprior Rural Institute — Kinloch Women's Rural Institute — Muckhart Women's Rural Institute — Ayr Bakers and Confectioners — Galashiels Trades Council — Burntisland Co-operative Women's Guild — Holytown Miners — Paisley Labour Party, Women's Section — Law Junction Miners — Paisley Building Trades — Prestongrange Miners — Crossgates Miners — Donibristle Miners — Shotts Miners — Glencraig Miners — Drumgoyne Women's Rural Institute — Muir of Ord Women's Rural Institute — Castletown Women's Rural Institute — Fort Augustus Women's Rural Institute — Nigg Women's Rural Institute — Pegrat Women's Rural Institute — Pennighael Women's Rural Institute — Killin Women's Rural Institute — Auchtermuchty Women's Rural Institute — Lochcarron Women's Rural Institute — Corpach Women's Rural Institute — Golspie Women's Rural Institute — Contin Women's Rural Institute — 200/B/3/2/C693/1/48